A Brief History of Biogas in Nepal: Lessons for the Future from the Past - Khadka, Aabhash; Parajuli, Anmol; Khadka, Aakash (Historical Journal, 2022)
Biogas, a gaseous mixture resulted from anaerobic digestion of organic matter, is an alternative source of energy that contributes to circularity. This paper introduces biogas and briefs its history in the context of Nepal. Despite being used as early as the 10th century BC, biogas only caught proper attention since the dawn of the industrial revolution. Meanwhile, biogas technology started its development only in the late-mid 19th century whilst taking a hundred more years for Nepal to follow suit. Since the construction of the first biogas plant in 1960, Nepal has introduced several plans and policies with the help of private and international agencies to construct about half a million biogas plants as of 2021. The major turning point in the history of biogas in Nepal came in 1992 with the initiation of Biogas Support Program which coincided with the then His Majesty Government of Nepal’s ambitious eight 5-year plan. The future policymakers are suggested to keep the growing urban population in mind whilst making new deals and policies to promote and facilitate biogas technology.